Green Investment Strategies and Export Performance: A Firm-level Investigation - Roberto Antonietti; Alberto Marzucchi (Fondazione Eni Enrico Mattei (FEEM), 2013)
In this paper we empirically investigate the relationship between investments in environmentally-oriented equipment and firms' export performance. Drawing on Porter hypothesis and firm heterogeneity theory, we adopt a structural model where first we estimate the impact of green investment strategies on the level of productive efficiency (TFP), and second we assess whether induced productivity influences the extensive and intensive margin of exports. Relying on a rich firm-level dataset on Italian manufacturing, our results show that firms with higher productivity, induced among other factors by green investment involving environmental protection and reduction in the use of raw materials, have increased commitment to, and profits from, exports, especially towards countries adopting a more stringent environmental regulatory framework. Our evidence provides a `green investment-based' explanation for the link between TFP-heterogeneity and trade.
Keywords: Q55; Q56; F14; F18; 330; Exports; Firm Heterogeneity; Green Investment Strategy; Total Factor Productivity